Efavirenz induced gynecomastia, hidden reality: a case series - Morkar, Dnyanesh N.; Aneja, Ankita; Agarwal, Rishabh (International Journal of Advances in Medicine, 2020)
The prognosis of HIV infection has considerably improved following the introduction of highly active anti-retroviral therapy by reducing AIDS related morbidity and mortality. At the same time, ART drugs are well known for their side effects. Gynaecomastia is a lesser known side effect of a commonly used anti-retroviral drug efavirenz. There are very few reports of HAART-induced gynaecomastia in resource-limited settings. The current study presents a series of three cases that developed ultrasound confirmed gynaecomastia following efavirenz containing HAART. Initial reports of gynaecomastia related to HAART were in HIV patients with lipodystrophy, they were termed as pseudogynaecomastia. Gradually, few reports of efavirenz related gynaecomastia were published wherein other causes of gynaecomastia were ruled out. Several hypothesis have been suggested for the pathophysiology of development of gynaecomastia related to efavirenz consumption. All other causes were ruled out in our patients too. The incidence of gynaecomastia is increasing in men with HIV on HAART therapy, proper identification and management will promote better drug adherence.